NEO MODERNISME ISLAM NURCHALISH MADJID (Relevansinya dengan Pembaruan Pendidikan Islam) - Syamsul Kurniawa M. Rais (The Pontianak State Institute of Islamic Studies, 2011)
In the context of Indonesian-ness, the emergence of neo Islamic modernism initiated by Nurchalish Madjid is a criticism as well as asolution to the two main streams of Islam: traditional and modern, which are always in an almost-endless conceptual discord. Neo Islamic modernism emerges to offer concepts that go beyond the two main streams. The emergence of neo Islamic modernism introduced by Nurchalish Madjid is a preliminary movement of modernization in terms of rationalization which serves to reform the old ways that are not in line with aqliyah. The reform Nurchalish Madjid brought in has touched many aspects such as religious matters, socio-politics and education. Nurchalish Madjid ideas on education are influenced by his way of thinking which is rational, realistic and relativistic. There fore, his view on education has paved the way to a new direction, by looking at the reality and the context of current condition. Thus, Nurchalish’s ideas on education have become a solution to the current educational problems such as dichotomy, weak aspect of methodology, unclear and imbalanced orientation of religious education, etc.